y=(x+1)(x-2)(x+3i)(x-3i)

Simple and best practice solution for y=(x+1)(x-2)(x+3i)(x-3i) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=(x+1)(x-2)(x+3i)(x-3i) equation:


Simplifying
y = (x + 1)(x + -2)(x + 3i)(x + -3i)

Reorder the terms:
y = (1 + x)(x + -2)(x + 3i)(x + -3i)

Reorder the terms:
y = (1 + x)(-2 + x)(x + 3i)(x + -3i)

Reorder the terms:
y = (1 + x)(-2 + x)(3i + x)(x + -3i)

Reorder the terms:
y = (1 + x)(-2 + x)(3i + x)(-3i + x)

Multiply (1 + x) * (-2 + x)
y = (1(-2 + x) + x(-2 + x))(3i + x)(-3i + x)
y = ((-2 * 1 + x * 1) + x(-2 + x))(3i + x)(-3i + x)
y = ((-2 + 1x) + x(-2 + x))(3i + x)(-3i + x)
y = (-2 + 1x + (-2 * x + x * x))(3i + x)(-3i + x)
y = (-2 + 1x + (-2x + x2))(3i + x)(-3i + x)

Combine like terms: 1x + -2x = -1x
y = (-2 + -1x + x2)(3i + x)(-3i + x)

Multiply (-2 + -1x + x2) * (3i + x)
y = (-2(3i + x) + -1x * (3i + x) + x2(3i + x))(-3i + x)
y = ((3i * -2 + x * -2) + -1x * (3i + x) + x2(3i + x))(-3i + x)
y = ((-6i + -2x) + -1x * (3i + x) + x2(3i + x))(-3i + x)
y = (-6i + -2x + (3i * -1x + x * -1x) + x2(3i + x))(-3i + x)
y = (-6i + -2x + (-3ix + -1x2) + x2(3i + x))(-3i + x)
y = (-6i + -2x + -3ix + -1x2 + (3i * x2 + x * x2))(-3i + x)
y = (-6i + -2x + -3ix + -1x2 + (3ix2 + x3))(-3i + x)

Reorder the terms:
y = (-6i + -3ix + 3ix2 + -2x + -1x2 + x3)(-3i + x)
y = (-6i + -3ix + 3ix2 + -2x + -1x2 + x3)(-3i + x)

Multiply (-6i + -3ix + 3ix2 + -2x + -1x2 + x3) * (-3i + x)
y = (-6i * (-3i + x) + -3ix * (-3i + x) + 3ix2 * (-3i + x) + -2x * (-3i + x) + -1x2 * (-3i + x) + x3(-3i + x))
y = ((-3i * -6i + x * -6i) + -3ix * (-3i + x) + 3ix2 * (-3i + x) + -2x * (-3i + x) + -1x2 * (-3i + x) + x3(-3i + x))

Reorder the terms:
y = ((-6ix + 18i2) + -3ix * (-3i + x) + 3ix2 * (-3i + x) + -2x * (-3i + x) + -1x2 * (-3i + x) + x3(-3i + x))
y = ((-6ix + 18i2) + -3ix * (-3i + x) + 3ix2 * (-3i + x) + -2x * (-3i + x) + -1x2 * (-3i + x) + x3(-3i + x))
y = (-6ix + 18i2 + (-3i * -3ix + x * -3ix) + 3ix2 * (-3i + x) + -2x * (-3i + x) + -1x2 * (-3i + x) + x3(-3i + x))

Reorder the terms:
y = (-6ix + 18i2 + (-3ix2 + 9i2x) + 3ix2 * (-3i + x) + -2x * (-3i + x) + -1x2 * (-3i + x) + x3(-3i + x))
y = (-6ix + 18i2 + (-3ix2 + 9i2x) + 3ix2 * (-3i + x) + -2x * (-3i + x) + -1x2 * (-3i + x) + x3(-3i + x))
y = (-6ix + 18i2 + -3ix2 + 9i2x + (-3i * 3ix2 + x * 3ix2) + -2x * (-3i + x) + -1x2 * (-3i + x) + x3(-3i + x))

Reorder the terms:
y = (-6ix + 18i2 + -3ix2 + 9i2x + (3ix3 + -9i2x2) + -2x * (-3i + x) + -1x2 * (-3i + x) + x3(-3i + x))
y = (-6ix + 18i2 + -3ix2 + 9i2x + (3ix3 + -9i2x2) + -2x * (-3i + x) + -1x2 * (-3i + x) + x3(-3i + x))
y = (-6ix + 18i2 + -3ix2 + 9i2x + 3ix3 + -9i2x2 + (-3i * -2x + x * -2x) + -1x2 * (-3i + x) + x3(-3i + x))
y = (-6ix + 18i2 + -3ix2 + 9i2x + 3ix3 + -9i2x2 + (6ix + -2x2) + -1x2 * (-3i + x) + x3(-3i + x))
y = (-6ix + 18i2 + -3ix2 + 9i2x + 3ix3 + -9i2x2 + 6ix + -2x2 + (-3i * -1x2 + x * -1x2) + x3(-3i + x))
y = (-6ix + 18i2 + -3ix2 + 9i2x + 3ix3 + -9i2x2 + 6ix + -2x2 + (3ix2 + -1x3) + x3(-3i + x))
y = (-6ix + 18i2 + -3ix2 + 9i2x + 3ix3 + -9i2x2 + 6ix + -2x2 + 3ix2 + -1x3 + (-3i * x3 + x * x3))
y = (-6ix + 18i2 + -3ix2 + 9i2x + 3ix3 + -9i2x2 + 6ix + -2x2 + 3ix2 + -1x3 + (-3ix3 + x4))

Reorder the terms:
y = (-6ix + 6ix + -3ix2 + 3ix2 + 3ix3 + -3ix3 + 18i2 + 9i2x + -9i2x2 + -2x2 + -1x3 + x4)

Combine like terms: -6ix + 6ix = 0
y = (0 + -3ix2 + 3ix2 + 3ix3 + -3ix3 + 18i2 + 9i2x + -9i2x2 + -2x2 + -1x3 + x4)
y = (-3ix2 + 3ix2 + 3ix3 + -3ix3 + 18i2 + 9i2x + -9i2x2 + -2x2 + -1x3 + x4)

Combine like terms: -3ix2 + 3ix2 = 0
y = (0 + 3ix3 + -3ix3 + 18i2 + 9i2x + -9i2x2 + -2x2 + -1x3 + x4)
y = (3ix3 + -3ix3 + 18i2 + 9i2x + -9i2x2 + -2x2 + -1x3 + x4)

Combine like terms: 3ix3 + -3ix3 = 0
y = (0 + 18i2 + 9i2x + -9i2x2 + -2x2 + -1x3 + x4)
y = (18i2 + 9i2x + -9i2x2 + -2x2 + -1x3 + x4)

Solving
y = 18i2 + 9i2x + -9i2x2 + -2x2 + -1x3 + x4

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = 18i2 + 9i2x + -9i2x2 + -2x2 + -1x3 + x4

See similar equations:

| k/6=8/16 | | log(x)+log(x+1)=2 | | 4(6)-4(3)+4(-3)= | | 3=1/2u | | 4(3-8)-5(-1-2)= | | p=25n-3500 | | 8-3(-6)+1(-4)= | | S=16t^2-676 | | 3x^2-4x+3=1 | | 3(x+1)+1+2x=4x+4+x | | -1=3x^2-4x+3 | | f(2)=5x^4-2x+8 | | 2/5b=750 | | f(1)=5x^4-2x+8 | | 2/10b=750 | | 2x^2-3x-5=10 | | f(x)=5x^4-2x+8 | | 12x^2+68+24=0 | | 2t=2 | | f(x)=5x^4-2x-8 | | -9y+4y=13-4y+4y | | X*x*x=88 | | 2X-3COSX=0 | | 1/4x+1/4=8 | | 1/4x+1/4=4 | | 256=x^2+12x | | 20+80+20x=40+80+20y | | -37=-7+10x | | 7(k-3)=3-5 | | 3y^2-x^2=25 | | -5a+4+6a=12-30 | | y^2-8y-24=0 |

Equations solver categories